Globalized Islam: The Search for a New Ummah by Olivier Roy (New York: Columbia University Press, 2004. 349 pages.) (American Journal of Islam and Society, 2006)
This book analyzes core issues of Islamic thought in the modern era byexamining Islam as both the dominant religion in the Middle East and aminority religion in the West. By considering a wide range of ideological, spiritual, and non-violent or violent events, Roy posits that contrary to popular(and erroneous) assumptions, Islamic fundamentalism derives fromglobalization, not from a clash of civilizations or religions.Roy claims that both liberalism and fundamentalism arise from globalizationand deterritorialization (i.e., the spread of Muslims and Islam beyondthe traditional Muslim world). He views neo-fundamentalists, Islamists,born-again Muslims, and radical violent groups as bit players in Islam’s continuingefforts to come to terms with western values. For example, Islamicmovements in Europe seem to be fundamentalist on the surface; but uponcloser examination, they display western values (e.g., individualization, selfrealization,spirituality, and the weakening of traditional ties and sources ofauthority). With one-third of all Muslims living outside Muslim-majoritylands, Roy believes that modern manifestations of Islam in the West (e.g.,radicalism, neo-fundamentalism, Sufism, nationalism, re-Islamization, neo-Islamic brotherhoods, and anti-westernism) evolve from globalizationinstead of a desire to return to orthodox religious practices or the allegedly“pure” Islam of an earlier time. He tells us that Islam is no longer only thetraditional faith of the Salaf (i.e., the three first and most pious generationsof Muslims), but also a mixture of modern sociological and cultural – evenwestern – elements, regardless of what modern-day Salafis claim ...